How to read a film : movies, media, and beyond : art, technology, language, history, theory - Monaco, James (Oxford University Press, 2009)
James Monaco discusses the elements necessary to understand how a film conveys its meaning, and, more importantly, how the audience can best discern all that a film is attempting to communicate.